2014
DOI: 10.1155/2014/716860
|View full text |Cite
|
Sign up to set email alerts
|

Cosmetic Outcome Assessment following Breast-Conserving Therapy: A Comparison between BCCT.core Software and Panel Evaluation

Abstract: Purpose. Over recent decades, no consensus has yet been reached on the optimal approach to cosmetic evaluation following breast-conserving therapy (BCT). The present study compared the strengths and weaknesses of the BCCT.core software with a 10-member panel from various backgrounds. Methods. Digital photographs of 109 consecutive patients after BCT were evaluated for 7 items by a panel consisting of 2 breast surgeons, 2 residents, 2 laypersons, and 4 plastic surgeons. All photographs were objectively evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 31 publications
3
66
1
3
Order By: Relevance
“…In other studies, the agreement between panel evaluation and BCCT.core has been measured using κ statistics. Haloua and colleagues and Heil et al . reported a level of agreement of 0·64 and 0·27 respectively.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In other studies, the agreement between panel evaluation and BCCT.core has been measured using κ statistics. Haloua and colleagues and Heil et al . reported a level of agreement of 0·64 and 0·27 respectively.…”
Section: Discussionmentioning
confidence: 90%
“…This clearly shows a methodological limitation. In a study by Haloua and co‐workers involving ten assessors, intraobserver agreement varied between 0·54 and 0·80. Vrieling and colleagues reported a weighted κ value of 0·70 for intraobserver agreement in a panel of five assessors.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014 Haloua et al reported BCCT.core results of excellent in 10 cases (9%), good in 54 (50%), fair in 34 (31%) and poor in 11 cases (10%) in a study cohort who had undergone BCT at least one year before the evaluation [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, two retrospective studies reported no correlation between objectively assessed cosmetic outcomes (Breast Analyzing Tool and Cosmesis Index) and quality of life . Computerized measurements are known to result in a significantly worse cosmetic outcome compared to patient and panel evaluation, with a fair to moderate agreement between BCCT.core and panel evaluation . Patient and panel evaluations are based on observer evaluation of the breast, taking into account specific factors, whereas some computerized measurements fail to include aspects such as scar appearance and color differences between breasts .…”
Section: Discussionmentioning
confidence: 99%
“…Although BCT is considered to be the least disfiguring choice in the surgical treatment of breast cancer, fair or poor cosmetic outcomes are still observed in up to one third of all patients and will negatively influence several aspects of QoL . At the current time, it is advisable to use both objective and subjective evaluation methods for cosmetic outcome assessment . Objective (computerized) methods have the advantage that they facilitate comparison of cosmetic outcomes between different studies and treatment methods.…”
Section: Introductionmentioning
confidence: 99%